Novel Methodology to Assess RF Performance of Co-located MIMO Radar Systems Transmitting Binary Phased Coded Waveforms - Colon-Diaz, Nivia; Janning, Dan; McCormick, Patrick M.; Aberle, James T.; Bliss, Daniel W. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this work an experimental radar testbed and dual directional couplers (DDC) are used to collect measurements of the forward and reverse waves at each element, its mutual coupling, and beam-patterns. The collected measured data is used to validate a methodology for assessing radio frequency (RF) performance of a co-located multiple-input multipleoutput (MIMO) radar system transmitting binary phased coded (BP) waveforms. The estimated and measured active reflection coefficient (ARC) and beam-patterns are presented. The effect of different excitations and mutual coupling on the radiated fields is also presented.